Coupling nearshore and aeolian processes: XBeach and duna process-based models - Roelvink, Dano (2020)
A new dune profile model, Duna, is developed and coupled with the existing XBeach model, in which some key improvements allow a much better behaviour of the intertidal beach and the inclusion of structural erosion or accretion through a longshore transport gradient. The model is shown to represent typical behaviour of a beach-dune system in Praia de Faro, Portugal and to be able to simulate processes on a decadal timescale. The model captures a balance between longshore gradients and cross-shore processes in the surf zone, competing effects of moderate conditions and storms in the intertidal area and between build-up by storm waves and aeolian transport on the berm. Vegetation behaviour is shown to play a key role in the development of the shape of the foredunes. The relation between progradation or recession rate and foredune height as often reported in literature is reproduced and explained.